A preliminary biochemical study of the mechanisms involved in the host-pathogen interaction between Pinus species and Sphaeropsis sapinea - Engelbrecht, Erika (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1997.